Climate change adaptation to extreme heat: a global systematic review of implemented action. Issue 1 (1st June 2021) - Turek-Hankins, Lynée L; Coughlan de Perez, Erin; Scarpa, Giulia; Ruiz-Diaz, Raquel; Schwerdtle, Patricia Nayna; Joe, Elphin Tom; Galappaththi, Eranga K; French, Emma M; Austin, Stephanie E; Singh, Chandni; Siña, Mariella; Siders, A R; et al.
Abstract: Extreme heat events impact people and ecosystems across the globe, and they are becoming more frequent and intense in a warming climate. Responses to heat span sectors and geographic boundaries. Prior research has documented technologies or options that can be deployed to manage extreme heat and examples of how individuals, communities, governments and other stakeholder groups are adapting to heat. However, a comprehensive understanding of the current state of implemented heat adaptations—where, why, how and to what extent they are occurring—has not been established. Here, we combine data from the Global Adaptation Mapping Initiative with a heat-specific systematic review to analyze the global extent and diversity of documented heat adaptation actions ( n = 301 peer-reviewed articles). Data from 98 countries suggest that documented heat adaptations fundamentally differ by geographic region and national income. In high-income, developed countries, heat is overwhelmingly treated as a health issue, particularly in urban areas. However, in low- and middle-income, developing countries, heat adaptations focus on agricultural and livelihood-based impacts, primarily considering heat as a compound hazard with drought and other hydrological hazards. 63% of the heat-adaptation articles feature individuals or communities autonomously adapting, highlighting how responses to date have largely consisted of coping strategies. The current global status of responses to intensifying extreme heat, largely autonomous and incremental yet widespread, establishes a foundation for informed decision-making as heat impacts around the world continue to increase.